Memlükler’de Kur’ân Tilâveti ve Kıraat İlmi - Gökdemir, Ahmet (FSM Vakıf Üniversitesi, 2021)
Makalede Memlükler’de Kur’ân tilâveti ile kıraat ilminin durumu ele alınmıştır. Konunun anlatımında genel hatlarıyla Memlükler’de ilmî ortama değinilmiş; daha sonra Kur’ân ve kıraat eğitiminin verildiği kurumlar, o dönemde yetişmiş önemli kıraat âlimleri, kadınların Kur’ân öğretimindeki yeri ile Memlükler’deki kıraat ilmine dair birikimin Osmanlı’ya etkisi incelenmiştir. Araştırmada Memlükler’le ilgili yazılmış madde, makale, tez ve müstakil kitapların yanı sıra o döneme yönelik bilgi veren tabakât kitaplarından istifade edilmiştir.

The paper deals with the status of Quran recitation and qiraah in Mamluks. While handling the subjects, firstly, the scientific environment in Mamluks was stated in broad strokes. Afterwards, the institutions where the Quran and recitation education were provided, notable qiraah scholars who were trained in that period, the role of women in teaching the Quran and the effect of qiraah accumulation in the Mamluks on the Ottoman were discussed. Aside from essays, articles, theses, and individual books written about the Mamluks, the tabaqat literature which is giving ideas about that period of time was also used during the analysis of the topics.
The Recitation and Qiraat of Quran in Mamluks
Keywords: Kur’ân; Tilâvet; Kıraat; Memlük; Osmanlı; Quran; Tilawah; Qiraah; Mamluk; Ottoman